Another light : Swedish art since 1945. - Granath, Olle (Stockholm : Swedish Institute Stockholm, 1982)
Andersson, Kjell ; Andersson, Torsten ; Aschenbrenner, Lennart ; Asker, Curt ; Baertling, Olle ; Bankier, Channa ; Bejemark, KG ; Bengtsson, Dick ; Billgren, Ola ; Bonniér, Olle ; Broström, Sverker ; Carlsund, Otto Gustav ; Contreras, Albert ; Cronqvist, Lena ; Cullberg, Erland ; Derkert, Siri ; Dietman, Erik ; Eklund, Sten ; Englund, Lars ; Eriksson, Elis ; Erixson, Sven ; Fahlström, Öyvind ; Figge, Eddie ; Franzén, John-e ; Fredriksson, Arne ; Friberg, Roj ; Frostensson, Karin ; Grate, Eric ; Gripenholm, Ulf ; Hagberg, Rune ; Hallström, Staffan ; Hatz, Félix ; Hillersberg, Lars ; Hillfon, Curt ; Hillfon, Hertha ; Hjorth, Bror ; Holmgren, Martin ; Hultén, Carl-Otto ; Hafström, Jan ; Höste, Einar ; Jansson, Rune ; Johansson, Albert ; Jones, Arne ; Karlung, Ake ; Kempe, Roland ; Kaks, Olle ; Kölare, Nils ; Landfors, Kjell ; Larsson, Bo ; Lindblom, Sivert ; Lindell, Lage ; Linder, Alf ; Lundquist, Evert ; Lyth, Harald ; Lövin, Björn ; Marklund, Bror ; Millhagen, Lars ; Mörner, Stellan ; Nemes, Endre ; Nilsson, Karl-Gustaf ; Nordenström, Hans ; Norlander, Ake ; Nyman, Olle ; Ohlin, Kjell ; Olofsson, Pierre ; Olson, Erik ; Pehrson, Karl Axel ; Petterson, Berndt ; Pettersson, Gun Maria ; Rahmberg, Ulf ; Regild, Carsten ; Rehnberg, Hakan ; Renberg, Margareta ; Renqvist, Torsten ; Reuterswärd, Carl Fredrik ; Rodhe, Lennart ; Rothman, Lenke ; Rydelius, Rune ; Samuelson, Ulrik ; Sandberg, Ragnar ; Schantz, Philip von ; Skott, Johan ; Strunke, Laris ; Svanberg, Max Walter ; Svedberg, Lena ; Tillberg, Peter ; Tjerned, Leif ; Trankell, Bo ; Ultvedt, Per Olof ; Wigert, Hans ; Viksten, Hans ; Wroblewski, Gregor ; Zennström, Petter ; Ängkvist, Olle ; Österlin, Anders ; Ostlihn, Barbro ; Östmar, Tommy
Duits
Engels
Frans
boek
Keywords: 1945-; Zweden